Dollar Will - McGhee, Alison, 1960- (New York : Atheneum, 2018)
Since his father's suicide, Will, sixteen, has mainly walked, worked at Dollar Only, and tried to replicate his father's cornbread recipe, but the rape of his childhood friend shakes things up.
"A Caitlyn Dlouhy Book."
Keywords: Grief -- Fiction; Stores, Retail -- Fiction; Fathers and sons -- Fiction; Rape -- Fiction; Suicide -- Fiction; Single-parent families -- Fiction